Synthesis and Characterisation of a Novel 2,3-O-di Acetyl-5,6-O-Benzylidene - L -Ascorbic Acid and its Complexes of Cr(III), Co(II), Ni(II),Cu(II) and Zn(II) - Al - Kadi, I. Sh. Abdul Razzaq (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
A new ligand type (O2) [2,3-O-diacetyl-5,6-O-benzylidene L- ascorbic acid] [L] and its complexes of general formula [M(L)2(X)(Y)]Cln (where: M=CrIII ,X=Y=H2O, n=3; CoII, X = Y = 0, n= 2; NiII and CuII, X = Cl, Y = H2O, n= 1; ZnII, X = Y = H2O,n = 2) are reported. The ligand was prepared in two steps; first step involved the synthesis of [5,6-O-benzylidene-L-ascorbic acid] (A). In second step derivative-A was then reacted with acetyl chloride and anhydrous pyridine as a base to give the titled ligand. Metal complexes of the ligand with CrIII,CoII,NiII,CuII and ZnII were synthesised by direct reaction of the corresponding metal chloride with the ligand[L] in a 2L:1M mole ratio. The ligand and its complexes were characterised by spectroscopic methods 1H NMR, FTIR, (UV-Vis), atomic absorption, microanalyses, chloride content, melting point and conductance measurements . These studies revealed that the geometry about CrIII, NiII,CuII and ZnII is octahedral while the complex of CoII adopts a tetrahedral geometry.